Effects of technology-enhanced active learning on the musical creativity of gifted students - Maba, Adem; Sakar, Mümtaz Hakan (Creativity Studies, 2025)
Technology-enhanced active learning increases not only gifted students’ interest in learning but also facilitates the promotion of their musical creativity. This study uncovers gifted students’ attitude toward technology-enhanced active learning and its effect on their musical creativity. This mixed-methods study used an experimental design followed by semi-structured interviews. We developed a control group (n = 19) and an experimental group (n = 21) of the randomly selected gifted students’ age of 11–13 years old from science and art centres institution at secondary schools in Turkey. We designed an intervention to deliver music curricula through technology-enhanced active learning for the experimental group and without technology-enhanced active learning for the control group. Three experts used a rubric to measure the musical creativity of gifted students. A pre-test and post-test indicated that there was an effect of technology-enhanced active learning on the musical creativity of gifted students. Semi-structured interviews with students also suggested that gifted students have positive attitude towards technology-enhanced active learning. Students have a positive attitude towards the technology-enhanced active learning approach owing to five reasons: finding education programs beneficial, self-expression, improvement in composing skills, improvement in using technology while composing, and eagerness to continue technology-enhanced active music learning.